Seaglider observations of equatorial Indian Ocean Rossby waves associated with the Madden‐Julian Oscillation. Issue 6 (12th June 2014) - Webber, Benjamin G. M.; Matthews, Adrian J.; Heywood, Karen J.; Kaiser, Jan; Schmidtko, Sunke
Abstract During the CINDY–DYNAMO field campaign of September 2011–January 2012, a Seaglider was deployed at 80°E and completed 10 north‐south sections between 3 and 4°S, measuring temperature, salinity, dissolved oxygen concentration, and chlorophyll fluorescence. These high‐resolution subsurface observations provide insight into equatorial ocean Rossby wave activity forced by three Madden‐Julian Oscillation (MJO) events during this time period. These Rossby waves generate variability in temperature O(1°C), salinity O(0.2 g kg−1), density O(0.2 kg m−3), and oxygen concentration O(10 μmol kg−1), associated with 10 m vertical displacements of the thermocline. The variability extends down to 1000 m, the greatest depth of the Seaglider observations, highlighting the importance of surface forcing for the deep equatorial ocean. The temperature variability observed by the Seaglider is greater than that simulated in the ECCO‐JPL reanalysis, especially at depth. There is also marked variability in chlorophyll fluorescence at the surface and at the depth of the chlorophyll maximum. Upwelling from Rossby waves and local wind stress curl leads to an enhanced shoaling of the chlorophyll maximum by 10–25 m in response to the increased availability of nutrients and light. This influence of the MJO on primary production via equatorial ocean Rossby waves has not previously been recognized.